The Effect Of Night Exercise In Reducing The Stress Level Of Housewives In Nganjuk District - Agustin Widyowati; Eko Purwanto; Cucun Setya Ferdina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Monotonous routines for housewives can cause boredom and stress, resulting in negative emotional feelings and impact on disharmony in the household. One way to reduce stress is by exercising. The purpose of this study was to analyze the effect of night sports on reducing stress levels in housewives. The study used a one group pre-post test design experimental design. The population is all housewives in Sumberkepuh Village, Tanjunganom District, Nganjuk Regency with a sample of 22 respondents, using a purposive sampling technique. The independent variable is night sports (aerobics) and the dependent variable is the level of stress. The data analysis used the Wilcoxon statistical test. The results showed significant results (p = 0.001 and mean rank 11.50), which means that there was a decrease in the stress level of housewives after exercising. It is hoped that housewives will have free time to exercise to avoid stress due to prolonged and monotonous household chores.